c-Abl Kinase Is a Regulator of αvβ3 Integrin Mediated Melanoma A375 Cell Migration. - Chunmei Zhang; Chao Yang; Ruifei Wang; Yang Jiao; Khamal Kwesi Ampah; Xiaoguang Wang; Xianlu Zeng (PLoS ONE, 2013)
Integrins are heterodimeric transmembrane receptors that physically link the extracellular matrix (ECM) to the intracellular actin cytoskeleton, and are also signaling molecules that transduce signals bi-directionally across the plasma membrane. Integrin regulation is essential for tumor cell migration in response to growth factors. c-Abl kinase is a nonreceptor tyrosine kinase and is critical for signaling transduction from various receptors. Here we show that c-Abl kinase is involved in A375 cell migration mediated by αvβ3 integrin in response to PDGF stimulation. c-Abl kinase colocalizes with αvβ3 integrin dynamically and affects αvβ3 integrin affinity by regulating its cluster. The interaction between c-Abl kinase and αvβ3 integrin was dependent on the activity of c-Abl kinase induced by PDGF stimulation, but was not dependent on the binding of αvβ3 integrin with its ligands, suggesting that c-Abl kinase is not involved in the outside-in signaling of αvβ3 integrin. Talin head domain was required for the interaction between c-Abl kinase and αvβ3 integrin, and the SH3 domain of c-Abl kinase was involved in its interaction with talin and αvβ3 integrin. Taken together, we have uncovered a novel and critical role of c-Abl kinase in αvβ3 integrin mediated melanoma cell migration.